A Model of Epigenetic Inheritance Accounts for Unexpected Adaptation to Unforeseen Challenges - Dino Osmanović; Yitzhak Rabin; Yoav Soen (Advanced Science)
Abstract Accumulated evidence of transgenerational inheritance of epigenetic and symbiotic changes raises fundamental questions about the possible types, significance and duration of impacts on the population, as well as whether, and under which conditions, the inheritance of non‐genetic changes confers long‐term advantage to the population. To address these questions, a population epigenetics model of individuals undergoing stochastic changes and/or induced responses that are transmitted to the offspringis introduced. Potentially adaptive and maladaptive responses are represented, respectively, by environmentally driven changes that reduce and increase the selective pressure. Analytic solutions in a simplified case of populations that are exposed to either periodic or progressively deteriorating environments shows that acquisition and transmission of non‐genetic changes that alleviate the selective pressure confer long‐term advantage and may facilitate escape from extinction. Systematic analysis of outcomes as a function of population properties further identifies a non‐traditional regime of adaptation mediated by stochastic changes that are rapidly acquired within a lifetime. Contrasting model predictions with experimental findings shows that inheritance of dynamically acquired changes enables rapid adaptation to unforeseen challenges and can account for population dynamics that is either unexpected or beyond the scope of traditional models.